2013
DOI: 10.1227/01.neu.0000429844.06955.39
|View full text |Cite
|
Sign up to set email alerts
|

The Pipeline Embolization Device

Abstract: PED therapy may have an acceptable safety-efficacy profile. The risk of complications appears to decrease dramatically with physician experience, supporting the existence of a learning curve. Patients with previously treated aneurysms have higher complication rates, whereas fusiform aneurysms achieve lower obliteration rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(36 citation statements)
references
References 9 publications
1
35
0
Order By: Relevance
“…Jabbour et al assessed the age, sex, aneurysm location, size, morphology, adjunctive use of coils, procedural complications and the angiographic follow-up time as predictors of aneurysm obliteration. 17 In their study, only fusiform aneurysms and a shorter follow-up duration negatively affected aneurysm occlusion rate. They also determined that the number of PEDs used was not a predictor of aneurysm obliteration, suggesting that the use of multiple PEDs provides no benefit in terms of angiographic obliteration, while unnecessarily increasing the procedural time, cost, and the risk of thromboembolic complications.…”
Section: Discussionmentioning
confidence: 86%
“…Jabbour et al assessed the age, sex, aneurysm location, size, morphology, adjunctive use of coils, procedural complications and the angiographic follow-up time as predictors of aneurysm obliteration. 17 In their study, only fusiform aneurysms and a shorter follow-up duration negatively affected aneurysm occlusion rate. They also determined that the number of PEDs used was not a predictor of aneurysm obliteration, suggesting that the use of multiple PEDs provides no benefit in terms of angiographic obliteration, while unnecessarily increasing the procedural time, cost, and the risk of thromboembolic complications.…”
Section: Discussionmentioning
confidence: 86%
“…In contrast to this study, Siddiqui et al reported less favorable results in a series of 7 large or giant vertebrobasilar fusiform aneurysms treated with flow diverters with significant morbidity and mortality; the poor outcome being secondary to post-treatment aneurysm ruptures in two and lack of neurological improvement caused by brainstem infarcts in another 2 patients [12]. Suboptimal outcome with the use of PED in fusiform aneurysms was also echoed in the study by Jabbour, et al in which they found fusiform aneurysm shape as a negative predictor for aneurysm obliteration despite a significantly higher number of PEDs (1.8) used in this subset of patients [10]. The variable results from different studies highlights the complexity associated with use of PED in vertebrobasilar fusiform aneurysms.…”
Section: Discussionmentioning
confidence: 95%
“…While the use of multiple PEDs appears intuitive in cases with fusiform aneurysms to decrease the shear stress on the diseased vessel wall, it may not obviate the chances of incomplete occlusion in these subgroup as seen in the study by Jabbour et al [10] and may unnecessarily increase procedural time, procedural cost, and the risk of thromboembolic complications [2]. On the other hand, a dense packing of the device during the implantation process does raise the degree of coverage resulting in larger flow diversion and a larger protective effect arguing in favor of implantation of more than one flow diverter across the orifice in order to increase the density with an improved flow diversion towards the parent artery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A steep learning curve is well recognized in performing FD deployments, and the deployment procedure requires substantial technical ability. 23 This is especially true for complex deployment techniques like compacting or overlapping FDs.…”
Section: Discussionmentioning
confidence: 99%